PENGARUH KUALITAS PRODUK, CITRA MEREK, DAN PERSEPSI HARGA TERHADAP PROSES KEPUTUSAN PEMBELIAN SEPEDA MOTOR HONDA SKUTIC BEAT DI DAELER JAYA ABADI BOJA KABUPATEN KENDAL PROVINSI JATENG - Luluk Santika, 14.05.51.0097; Prabowo, Rokh Eddy (Students' Journal of Economic and Management, 2018)
This study aims to determine the effect of each product quality variable, brand image, and price perception on the process of purchasing decisions of a Honda skutic motorcycle at Daeler Jaya Abadi Boja, District Kendal, Province Jateng. The population in this study are all buyers of Honda Skutic Beat motorcycle with a sample of 100 people. Primary data is processed using SPSS version 19 program. The results of the data show that all indicators are valid and reliable. Each variable positively and significantly affect the purchasing decision process of Honda Skutic beat motorcycle. Ability of the four variables in explaining the decision to buy a motorcycle Skutic Honda only 67.8 percent, the rest is determined by other variables such as promotion. Keywords: product quality, brand image, price perception, purchasing decision process